COVID-19 risk, attitudes and behaviour study (CRAB study): A knowledge, attitudes, and practise qualitative study of COVID-19 in the Royal Navy - Woolley, Stephen D.; Chambers, Robert; Bishop, Jonathan R. B.; Logan, Amy; McMillan, Peter; Fletcher, Thomas E.; Taegtmeyer, Miriam; O'Shea, Matthew K. (Frontiers in Public Health, 2023)
Introduction Outbreaks of SARS-CoV-2 onboard maritime platforms spread rapidly and have high attack rates. The aim of the COVID-19 Risk, Attitudes and Behaviour (CRAB) study was to investigate the knowledge, attitudes, and practises in the Royal Navy in relation to COVID-19 prevention. Methods The CRAB study was a cross-sectional survey, using a census sampling method, conducted in May and June 2021. An online questionnaire was distributed to all serving Royal Navy regular personnel using either the MyNavy application or via a QR code through email for a continuous 14 day period. The questionnaire was based on an existing validated questionnaire used for avian influenza epidemics. Questions investigated individual perceptions of COVID-19 seriousness, compliance with prevention methods, explored vaccination intention and vaccine hesitancy (unvaccinated individuals who declined or were unsure about receiving a COVID-19 vaccine). The chi-squared test of best fit was used to compare the demographic responses against the whole organisation, with p-value < 0.05 deemed significant. Odds ratios were used to investigate associations between demographic groups and responses to questions, with an odds ratio crossing 1.0 deemed non-significant. Results The response rate was 6% (2,080/33,200), with 315 responses collated in the pilot phase and 1,765 in the main study phase. Male participants were less likely to rate COVID-19 as serious (OR 0.34; 95% CI: 0.23–0.49). BAME ethnicity (OR 2.41; 95% CI: 1.12–5.17) rated it as more serious. At the time of the study 62% of respondents had received one dose of a COVID-19 vaccine. In the 797 unvaccinated personnel, vaccine hesitancy accounted for 24.2% (193/797), of whom 136 were white males. Those who had a higher COVID-19 serious rating, the most significant factor for non-adherence to COVID-19 prevention measures in both vaccinated (OR 1.61 [95%CI: 1.20–2.17]) and vaccine-hesitant (OR 3.24 [95%CI: 1.63–6.41]) individuals was colleagues' non-adherence. The most trusted source of information on vaccines was provided by the Defence Medical Services (77.2% [1,606/2,080]). Conclusion This study has identified reasons for COVID-19 protective measure adherence, sources of information trusted by respondents and vaccine hesitancy, in the Royal Navy. The questionnaire can be used to investigate attitudes and behaviours in future emerging infectious diseases.